Brittleness Index of High-Rank Coal Reservoir and Its Influencing Factors in Mabidong Block, Qinshui Basin, China. (8th May 2021) - Zhang, Yixuan; Meng, Yanjun; Hao, Panyun; Shang, Yanjie; Fu, Xinyu
Abstract : Brittleness index is an important mechanical index to evaluate the fracturability of conventional oil and gas reservoirs. However, the brittleness index of an organic coal reservoir is more complex. In this study, based on array sonic logging and density logging data, coal brittleness index is calculated using an elastic parameter method in the Mabidong coalbed methane (CBM) block in southern Qinshui Basin. In combination with coal-body structure observation, the maceral analysis, and proximate data of coal cores, a comprehensive study of geological influencing factors of coal brittleness index has been carried out. According to coal fragmentation degree, the coal-body structure of coal seams can be divided into primary, cataclastic, and granulate structure. The average interval of brittleness index of primary, cataclastic, and granulate structural coals is 63.3-71.48, 73.01-74.85, and 77.41-82.77, respectively. The results indicate that generally the order of brittleness index is primary structural coal < cataclastic structural coal < granulate structural coal. Young's modulus and the brittleness index have a good positive correlation. Poisson's ratio and the brittleness index are negatively correlated in No. 3 coal seam but are positive correlated in No. 15 coal seam. The vitrinite content is positively correlated with brittleness index, and the inertinite content is negatively correlated. For the primary and cataclastic structure coal, the ash and volatile is positively correlated with the brittleness index. The correlation of brittleness index, macerals, and coal quality parameters in the primary structure coal is better than that of the cataclastic and granulate structure coal. The research results are helpful to guide the coal brittleness index and coal-body structure prediction in fracturing of CBM wells.